2008
DOI: 10.1108/00070700810858691
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological innovations in kefir production: a review

Abstract: PurposeThe purpose of the paper is to show that traditionally, kefir was obtained by fermenting milk with kefir grains. Wide variation in microflora of kefir grains makes it difficult to obtain an optimal and uniform starter culture necessary for obtaining a quality kefir. Reviewed literature on microbiological and technological innovations in kefir production would enrich the scientific knowledge resulting in production of kefir with superior physical, chemical, nutritional, therapeutic and sanitary qualities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 45 publications
1
26
0
10
Order By: Relevance
“…Traditional kefir made from caprine milk was found to have a low viscosity and sensory properties unlike those of bovine kefir and contained 0.04-0.3% ethanol (Sarkar, 2008). Tratnik et al (2006) found that the ethanol content in bovine and caprine kefir enriched with whey protein concentrate was 0.32 and 0.35%, respectively.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional kefir made from caprine milk was found to have a low viscosity and sensory properties unlike those of bovine kefir and contained 0.04-0.3% ethanol (Sarkar, 2008). Tratnik et al (2006) found that the ethanol content in bovine and caprine kefir enriched with whey protein concentrate was 0.32 and 0.35%, respectively.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Kefir microfloral composition varies according to culture medium and production method (Sarkar, 2008).…”
Section: Microbiological Characteristicsmentioning
confidence: 99%
“…The fermentation agent of kefir known as the "kefir grain" is a gelatinous mass of protein and polysaccharide structure containing a variety of species of lactic acid bacteria, acetic acid bacteria, and yeasts, which make up a natural microbial ecosystem (Farnworth, 2005;Guzel-Seydim et al, 2011;Montanuci et al, 2012;Sarkar, 2008). Due to the large quantity and complex nature of the associations between the species involved, the microflora of kefir grains has not been fully elucidated yet (Pogačić et al, 2013).…”
Section: Kefirmentioning
confidence: 99%
“…Traditionally, kefir is produced by inoculating kefir grains in milk for 18 to 24h at a temperature of 20 to 25 °C (Leite et al, 2013;Sarkar, 2008). At the end of the fermentation process, the kefir grains are recovered and reused, a step which is different from those in the production of other fermented milk products.…”
Section: Kefirmentioning
confidence: 99%
See 1 more Smart Citation